Relating microbiological and physicochemical patterns of a traditional Portuguese fermented sausage along processing - Pereira, Ana Paula (2018)
Linguiça is a Portuguese popular ready-to-eat dry fermented sausage. Despite the high diversity of sausages produced in Portugal, all of them are made from cut pork meat macerated with water, wine, salt, garlic, pepper, and undergoes processes of maturation, smoking and drying. During the fermentation and drying of sausages, L. monocytogenes tends to decrease considerably. However, despite the various hurdles in the dry sausage manufacturing process, this foodborne pathogen is able to survive and is detected in the final product. Factors that may affect the growth or survival of foodborne pathogens in sausage products such as linguiça include water activity (aw), pH, temperature, use of starter cultures and use of ingredients with antimicrobial activity (e.g., garlic, smoke). The present study has evaluated the influence of the addition of a commercial starter culture and ripening temperature (10º C and 18ºC) on growth and survival of L. monocytogenes strains, isolated from sausage, in experimentally inoculated linguiça. Sliced raw meat was mixed with salt (20g/kg), dry garlic (4,5g/kg), sweet paper (12,5g/kg), laurel (0,5g/kg), dextrose (10g/kg), a mix of red/white wine (410ml/kg) and water (410ml/kg) and inoculated with L. monocytogenes (5 log10/g). Additionally Commercial starter culture (5 log10/g) was added to one batch. The batter was macerated for 3 days at 4ºC. After stuffing into natural pork casings, sausages were hung vertically in a climate controlled chamber, for ripening at 10℃ or 18ºC with 83% relative humidity (RH) during ten days. During maceration step was observed no changes in growth rate of LAB and L. monocytogenes. However during ripening step was verified an increase of the count of LAB and a concomitantly decrease of L. monocytogenes. In the batches not inoculated with a commercial starter culture was observed a decrease of L. monocytogenes of 1 log10/g at 10ºC and 1,57log10/g at 18ºC of ripening temperature. The addition of a commercial starter culture increased the reduction of pathogen at both temperatures (1,57log10/g at 10ºC and 2,24log10/g at 18ºC). This study points out the fact that the decrease of L. monocytogenes contamination rate during the manufacturing process of sausages is due to the drying and ripening step than to the maceration itself and is due mainly to the effect of starter culture and ripening temperature.